2013
DOI: 10.1017/s1041610213001142
|View full text |Cite
|
Sign up to set email alerts
|

The development and evaluation of the DK-20: a knowledge of dementia measure

Abstract: The DK-20 is the first knowledge of dementia measure to be developed specifically for unqualified care staff and has reasonable psychometric properties. It may be used to identify gaps in knowledge, highlighting areas for inclusion in educational interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 22 publications
4
39
0
Order By: Relevance
“…Although dementia-specific training has been found to improve knowledge of dementia (Smyth et al, 2013), several studies have found that knowledge of dementia was not associated with a sense of competence in dementia care (Schepers et al, 2012;Shanahan, Orrell, Schepers, & Spector, 2013). An evaluation of a nurse aide education program to improve communication with patients with dementia found improved knowledge, but comfort and perceived skill did not improve (Beer, Hutchinson, & Skala-Cordes, 2012).These findings suggest that improving competence requires more than improving knowledge of dementia.…”
Section: Implications For Continuing Education Strategies and Future mentioning
confidence: 99%
See 1 more Smart Citation
“…Although dementia-specific training has been found to improve knowledge of dementia (Smyth et al, 2013), several studies have found that knowledge of dementia was not associated with a sense of competence in dementia care (Schepers et al, 2012;Shanahan, Orrell, Schepers, & Spector, 2013). An evaluation of a nurse aide education program to improve communication with patients with dementia found improved knowledge, but comfort and perceived skill did not improve (Beer, Hutchinson, & Skala-Cordes, 2012).These findings suggest that improving competence requires more than improving knowledge of dementia.…”
Section: Implications For Continuing Education Strategies and Future mentioning
confidence: 99%
“…An evaluation of a nurse aide education program to improve communication with patients with dementia found improved knowledge, but comfort and perceived skill did not improve (Beer, Hutchinson, & Skala-Cordes, 2012).These findings suggest that improving competence requires more than improving knowledge of dementia. Shanahan et al (2013) offer the explanation that knowledge is more objective and fact-based, whereas competence is a subjective feeling of confidence, and that it is possible to know how to do something without feeling competent at it. There is growing recognition that sustained implementation of knowledge and skills gained from both entry-level and continuing education programs for healthcare providers caring for people with dementia must be accompanied by ongoing organizational support and embedded in organizational structures (McCormack et al, 2013;Smythe, Bentham, Jenkins, & Oyebode, 2015).…”
Section: Implications For Continuing Education Strategies and Future mentioning
confidence: 99%
“…(c) Knowledge was measured using the Dementia Knowledge -20 scale. 115 This consists of 20 questions for which there are five possible answers. The scale has sufficient reliability and was administered at baseline and final follow-up only.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…To understand the level of dementia knowledge, the Dementia Knowledge -20 scale 115 was used at baseline and follow-up 2 only. Within the scale there are two subdomains, dementia core knowledge and DOI: 10.3310/pgfar05050 PROGRAMME GRANTS FOR APPLIED RESEARCH 2017 VOL.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…Other, for example, occupational therapist or physiotherapist To enhance future evaluations of the training programme the 20-item dementia knowledge questionnaire DK-20 (Shanahan et al 2013) and the sense of competence in dementia care staff scale (Schepers et al 2012) will be used before and after each training course to assess whether knowledge of dementia has improved.…”
Section: %mentioning
confidence: 99%